Batas Pertanggungjawaban Notaris atas Pembuatan Akta Otentik - Ahmad Farich Sultoni (Jurnal Ilmu Kenotariatan, 2021)
Notary profession is a profession that provides legal protection and certainty for justice seekers. This profession is inherent in various people's lives in several sectors, such as business, banking, property and others. therefore, the importance of notary competence in the making of deed must be further enhanced given the complexity of the demands of his position in providing solutions to the community regarding the needs arising from alliances, especially in the making of deeds that become very vital. Because, notary public must be responsible for the authentic deed to the parties. So the principle of prudence must be properly applied by a notary public. Many notaries must be responsible for their errors or omissions caused by the making of authentic deed that is problematic, defective or not in accordance with the laws and regulations.